PENGENDALIAN KUALITAS PROSES EDIT PROGRAM PENGERJAAN MOULD: STUDI KASUS PT ASTRA HONDA MOTOR - A., Anggara Hayun (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Time process to make molding is highly influenced by machining process. So to increase productivity, it must be avoided the machining lost time from production process. Therefore, it needs control to the usage of machine. As a control that had been done is to find main cause factor why cnc machine runs unproperly, by sampling method to measure lost time happened in order to get optimum condition. The result of the activity shows how long lost time can be tolerated.